Studi Perencanaan Sumur Injeksi Dalam Upaya Penanggulangan Genangan Di Kawasan Perkotaan (Studi Kasus Di RW. 8 Dan 9 – Kelurahan Blimbing, Kota Malang) - Syafira, Annisa Zuyyinani'ma; Bisri, Mohammad; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2021)
RW.8 and 9 areas, Blimbing Sub-district, Malang city is one of the areas that often occur inundation due to changes in land cover and narrowing of drainage channels. The solution is the manufacture of injection wells to determine the inundation, planning, and effectiveness of injection wells at the research site. To analyze it, modeling rain inundation a return period of 2 years and 5 years using Storm Water Management Model (SWMM) 5.1 application. Calibration results showed for the Root Mean Square Error (RMSE) value, modeling discharge and measurable discharge for a return period of 2 years is 17.3%, and a return period of 5 years is 20.9%. The simulation results showed the capacity of existing drainage channels for a return period of 2 years and 5 years resulted in 8 channels overflowing from 42 existing channels with the number of injection wells needed as many as 45 injection wells for 8 water catchment areas. The effectiveness value of the application of injection wells using rain barrels obtained results for a return period of 2 years is 66.67%-93.33% with average injection well effectiveness is 84.66% and a return period of 5 years is 66%-95% with average injection well effectiveness is 84.78%.